2020
DOI: 10.18584/iipj.2020.11.2.10574
|View full text |Cite
|
Sign up to set email alerts
|

The Institutionalisation of Sami Interest in Municipal Comprehensive Planning: A Comparison Between Norway and Sweden

Abstract: The Sami are recognized as an Indigenous people and a national minority in both Norway and Sweden, and their involvement in any planning concerning their traditional territories is required. The aim of this article is to examine how Sami interests are secured and institutionalized in municipal comprehensive planning (MCP). We use two case study areas: Sortland municipality in Norway and Vilhelmina municipality in Sweden. Analysis of various qualitative materials indicates that, despite contextual and instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…65 In practice, the municipal comprehensive plans are drafted in accordance with public and national interests and comply with environmental standards (including those mentioned in the Environmental Code) but are de facto also influenced by the political interests of the parties in power. 66 In this regard, even though the municipalities' decisions are constrained by legal and policy imperatives, a number of studies have demonstrated that municipalities have a large margin of discretion in wind power planning and therefore play a key role in determining the outcome of the permit procedure. 67 The CAB, the courts and the state also have the capacity to influence the process, especially when they are responsible for making assessments and decisions on how to weigh up opposing interests.…”
Section: The Framework For Wind Energy Permits In Swedenmentioning
confidence: 99%
See 1 more Smart Citation
“…65 In practice, the municipal comprehensive plans are drafted in accordance with public and national interests and comply with environmental standards (including those mentioned in the Environmental Code) but are de facto also influenced by the political interests of the parties in power. 66 In this regard, even though the municipalities' decisions are constrained by legal and policy imperatives, a number of studies have demonstrated that municipalities have a large margin of discretion in wind power planning and therefore play a key role in determining the outcome of the permit procedure. 67 The CAB, the courts and the state also have the capacity to influence the process, especially when they are responsible for making assessments and decisions on how to weigh up opposing interests.…”
Section: The Framework For Wind Energy Permits In Swedenmentioning
confidence: 99%
“…71 In this context, Sámi interests can be safeguarded, but in many cases other economic interests are promoted at the expense of Sámi interests. 72 Similarly, the Environmental Code requires developers to consult with private individuals who are likely to be affected at an early stage and within the context of environmental impact assessment. 73 However, reindeer herders are considered to be the same as other individuals and the Swedish legal framework leaves a wide margin of appreciation to the developers about the way to organize and implement consultations.…”
Section: The Lack Of Procedural Rights For Sámi Reindeer Herdersmentioning
confidence: 99%
“…Coniferous forests (Pinus sylvetris, Picea abies) with elements of deciduous forests characterize the foothill boreal forest below the tree line. The Swedish mountain region encompasses 15 different municipalities, pre-dominantly rural with low population density, rich in natural resources, nature conservation, and tourism values, and with the presence of indigenous Sami culture reindeer husbandry as an exceptional characteristic [37,45,52]. The number of residents in the study region is close to With a focus on the mountain region, we analyzed the data on four levels (also see Table 2).…”
Section: Study Region and Sub-regionsmentioning
confidence: 99%
“…involve all types of land, and their use of this land is based on property rights and the right of public access in non-commercial as well as in commercial contexts. Reindeer husbandry is ongoing across the entire mountain area, and the Sami have both cultural rights and rights to self-determination in the mountain region, as the region constitutes a central part of the Sami traditional territories [34]. Consequently, it is obvious that nature and natural resources in the mountains are used for many purposes by numerous actors; this calls for coordination and collaboration [35,36].…”
Section: Research Design Study Area and Background Contextmentioning
confidence: 99%